Hidratação enteral administrada em fluxo contínuo em asininos (equus asinus africanus) desidratados experimentalmente. - Santos, João Paulo Albuquerque dos (2019)
The present study evaluated the effects of two continuous flow nasogastric enteric electrolyte maintenance solutions on physiological, hematological, biochemical and urinary parameters in dehydrated donkeys. Six donkeys were used in a cross-over design (6x2), kept under water and food fasting for 36 hours, together with single dose administration of furosemide 2 mg kg-1 intravenously, with mild to moderate dehydration expected. and subsequently submitted to 12 hours of continuous flow enteral hydration. The enteral hydration protocol did not change the physiological parameters, provided an increase of approximately 11% of body weight, brought an increase of more than 7% in the abdominal circumference, did not increase the feces moisture. The results obtained in weight gain and waist circumference show that the solutions used were effective in promoting the recovery of body mass of animals. However, SEMalt solution was more effective in reaching the bloodstream and causing greater hemodilution. The solutions were able to promote the supply of glucose, potassium and calcium to the animals of this study.